Naturally colored cotton for wearable applications - Naoumkina, Marina; Hinchliffe, Doug J.; Thyssen, Gregory N. (Frontiers in Plant Science, 2024)
Naturally colored cotton (NCC) offers an environmentally friendly fiber for textile applications.Processing white cotton fiber into textiles requires extensive energy, water, and chemicals, whereas processing of NCC skips the most polluting activity, scouring-bleaching and dyeing; therefore, NCC provides an avenue to minimize the harmful impacts of textile production. NCC varieties are suitable for organic agriculture since they are naturally insect and disease-resistant, salt and drought-tolerant. Various fiber shades, ranging from light green to tan and brown, are available in the cultivated NCC (Gossypium hirsutum L.) species. The pigments responsible for the color of brown cotton fiber are proanthocyanidins or their derivatives synthesized by the flavonoid pathway. Due to pigments, the NCC has excellent ultraviolet protection properties. Some brown cotton varieties exhibited superior thermal resistance of fiber that can be used to make fabrics with enhanced flame retardancy. Here, we review molecular mechanisms involved in the pigment production of brown cotton and challenges in breeding NCC varieties with a wide range of colors but without penalty in fiber quality. Also, we discuss opportunities for NCC with flame-retarding properties in textile applications.